The Proangiogenic Potential of Rat Adipose-Derived Stromal Cells with and without Cell-Sheet Induction: A Comparative Study - Xiaoru Xu; Shuang Song; Xiangdong Liu; Yuchao Zhou; Shaojie Shi; Guoqiang Zhao; Xingxing Wang; Xutao Chen; Wenshuang Zhao; Sijia Zhang; Wei Ma; Yingliang Song (Stem Cells International)
A functional vasculature for survival remains a challenge for tissue regeneration, which is indispensable for oxygen and nutrient supply. Utilizing mesenchymal stromal cells (MSCs) to alleviate tissue ischemia and repair dysfunctional or damaged endothelium is a promising strategy. Compared to other populations of MSCs, adipose-derived stromal cells (ASCs) possess a more significant proangiogenic potential and are abundantly available. Cell sheet technology has recently been widely utilized in bone engineering. Compared to conventional methods of seeding seed cell suspension onto biological scaffolds, cell sheet technology prevents cell loss and preserves the extracellular matrix (ECM). Nevertheless, the proangiogenic potential of ASC sheets remains unknown. In this study, rat ASC sheets were constructed, and their macro- and microstructures were examined. In addition, we investigated the effects of ASCs and ASC sheets on the biological properties and angiogenic capacity of endothelial cells (ECs). The results demonstrated that the ASC sheets gradually thickened as the number of cells and ECM increased over time and that the cells were in an active state of secretion. Similar to ASC-CM, the conditioned medium (CM) of ASC sheets could significantly enhance the proliferative capacity of ECs. ASC sheet-CM has significant advantages over ASC-CM in promoting the migration and angiogenesis of ECs, where the exosomes secreted by ASC sheets play an essential role. Therefore, using ASC sheets for therapeutic tissue and organ regeneration angiogenesis may be a valuable strategy.